How does goal orientation affect employees’ innovation behavior: Data from China - Zhen, Meirong; Cao, Jinru; Wang, Mi (Frontiers in Psychology, 2022)
The study takes an interaction perspective to examine possible interaction effects of goal orientation, psychological capital and organizational innovation climate aimed at enhancing employees’ innovation behavior. A total sample of 398 employees was selected in Chinese enterprises. The descriptive statistical analyses, multiple regression and bootstrap approach are adopted to test the interactive effects after controlling for gender, age, years for work of employees, type of enterprises and industry. Results indicate that learning goal orientation and proving goal orientation have a positive effect on employees’ innovation behavior through psychological capital. The positive relationship between psychological capital and employees’ innovation behavior is stronger when employees perceive more organizational innovation climate. Additionally, the positive effect of learning goal orientation and proving goal orientation on employees’ innovation behavior is stronger in high organizational innovation climate through high-level psychological capital than in low organizational innovation climate. However, the negative effect of avoiding goal orientation on innovation behavior is not significant. Finally, implications and further research are discussed.